2004
DOI: 10.1111/j.1475-3588.2004.00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Providing Specialist Psychological Support to Foster Carers: A Consultation Model

Abstract: Background: The task of fostering today is a complex one and foster carers need good quality support. This paper discusses a consultation service for foster carers. Method: It draws upon our qualitative experiences to explore the important themes that have emerged during the provision of the consultation service. Results: Foster carers are highly satisfied with the consultation service, which provides them with improved levels of access to psychological advice, a different understanding of the children, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 8 publications
2
29
0
Order By: Relevance
“…As stated earlier in the literature review, fostering adolescents can be both a satisfying and complicated endeavor (e.g., Lipscombe et al, 2003;Sallnäs et al, 2004). Foster parents and teens need support in managing behaviors resulting from a history of maltreatment and complex relationships associated with entering the child welfare system later in childhood (Farmer et al, 2005;Golding, 2004). When foster parents felt services were lacking, some cited this as a reason for not choosing to foster a teen.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As stated earlier in the literature review, fostering adolescents can be both a satisfying and complicated endeavor (e.g., Lipscombe et al, 2003;Sallnäs et al, 2004). Foster parents and teens need support in managing behaviors resulting from a history of maltreatment and complex relationships associated with entering the child welfare system later in childhood (Farmer et al, 2005;Golding, 2004). When foster parents felt services were lacking, some cited this as a reason for not choosing to foster a teen.…”
Section: Discussionmentioning
confidence: 92%
“…Lipscombe, Farmer, and Moyers (2003) identified four strategies common to parents fostering adolescents, which did not vary based on behavior: (a) setting and maintaining appropriate boundaries, (b) providing higher rates of supervision, (c) responding with sensitivity to the youth's developmental age, and (d) extending warmth and acceptance toward the youth. Providing social services and education to foster parents has also been found to increase their understanding of the youth they serve while offering ongoing support and guidance (Golding, 2004).…”
Section: Successful Fostering Of Adolescentsmentioning
confidence: 99%
“…The role of a cultural knowledge holder employed by the agency has been described in the literature as a benefit to foster parents before and during placement for advice on cultural matters with their foster child (Golding 2004;Moody and Chysko 2007). However, foster parents reported that more than one individual or position within the agency should be aware of and responsive to cultural matters of the children served by the agency.…”
Section: Cluster Two: Agency Supportmentioning
confidence: 98%
“…Such specialized support may increase foster parents knowledge of their children's ways, as well as their comfort in addressing cultural differences within their homes and advocacy in the community. Indeed, support from a cultural resource person contributes to awareness and utilization of local resources and assists with development of culturally appropriate expectations among foster parents (Golding 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Given that the research evidence suggests that children in care are prone to a range of difficulties, of which mental health problems are just one, this suggests the need for a more general support service for carers. Golding (2003Golding ( , 2004 describes the work of a multi-disciplinary team designed to support foster carers through the use of a consultation service. The service provides a way in which carers can meet with a clinical or educational psychologist, along with other relevant professionals such as social workers, to discuss the needs of the young people in their care, as well as their own needs.…”
Section: Support For Carersmentioning
confidence: 99%